Large Scale Expansion of Organic Farming at Risk of Phosphorus Limitation in the Long Run - Josephine Demay; Bruno Ringeval; Pietro Barbieri; Sylvain Pellerin; Thomas Nesme (Global Change Biology, 2026)
Debates about the agronomic feasibility of feeding the world organically have often focused on potential nitrogen (N) limitations, overlooking the challenges raised by the availability of phosphorus (P) in soils. Here we address this missing piece by simulating, over a 100‐year time span, a 100% organic world, in which mineral fertilizers are banned. We show that, in the short term, soil available P would barely limit organic crop production due to (i) existing soil P stocks, (ii) a replenishment of the available P pool by more stable pools, and (iii) a strong N limitation that reduces crop yields and consequently plant P demand. Conversely, in the long term (~100 years), the simulated 60% drop in cropland soil available P would result in a −12% reduction in cropland production globally, ranging from −4% in Eastern Europe to −29% in Latin America. This P limitation would be greater in places with high yields and a high proportion of legumes in crop rotations, highlighting the need to address N‐P interactions simultaneously to design more sustainable food systems. The expansion of organic farming therefore runs the risk of slowly but surely depleting soil P unless measures are taken to recycle all P flows within the agri‐food system.

Soil parent material—A major driver of plant nutrient limitations in terrestrial ecosystems - Laurent Augusto; David L. Achat; Mathieu Jonard; David Vidal; Bruno Ringeval (Global Change Biology, 2017)
Because the capability of terrestrial ecosystems to fix carbon is constrained by nutrient availability, understanding how nutrients limit plant growth is a key contemporary question. However, what drives nutrient limitations at global scale remains to be clarified. Using global data on plant growth, plant nutritive status, and soil fertility, we investigated to which extent soil parent materials explain nutrient limitations. We found that N limitation was not linked to soil parent materials, but was best explained by climate: ecosystems under harsh (i.e., cold and or dry) climates were more N‐limited than ecosystems under more favourable climates. Contrary to N limitation, P limitation was not driven by climate, but by soil parent materials. The influence of soil parent materials was the result of the tight link between actual P pools of soils and physical–chemical properties (acidity, P richness) of soil parent materials. Some other ground‐related factors (i.e., soil weathering stage, landform) had a noticeable influence on P limitation, but their role appeared to be relatively smaller than that of geology. The relative importance of N limitation versus P limitation was explained by a combination of climate and soil parent material: at global scale, N limitation became prominent with increasing climatic constraints, but this global trend was modulated at lower scales by the effect of parent materials on P limitation, particularly under climates favourable to biological activity. As compared with soil parent materials, atmospheric deposition had only a weak influence on the global distribution of actual nutrient limitation. Our work advances our understanding of the distribution of nutrient limitation at global scale. In particular, it stresses the need to take soil parent materials into account when investigating plant growth response to environment changes.

Phosphorus in agricultural soils: drivers of its distribution at the global scale - Bruno Ringeval; Laurent Augusto; Hervé Monod; Dirk van Apeldoorn; Lex Bouwman; Xiaojuan Yang; David L. Achat; Louise P. Chini; Kristof Van Oost; Bertrand Guenet; Rong Wang; Bertrand Decharme; et al. (Global Change Biology, 2017)
Phosphorus (P) availability in soils limits crop yields in many regions of the World, while excess of soil P triggers aquatic eutrophication in other regions. Numerous processes drive the global spatial distribution of P in agricultural soils, but their relative roles remain unclear. Here, we combined several global data sets describing these drivers with a soil P dynamics model to simulate the distribution of P in agricultural soils and to assess the contributions of the different drivers at the global scale. We analysed both the labile inorganic P ( P ILAB ), a proxy of the pool involved in plant nutrition and the total soil P ( P TOT ). We found that the soil biogeochemical background corresponding to P inherited from natural soils at the conversion to agriculture ( BIOG ) and farming practices ( FARM ) were the main drivers of the spatial variability in cropland soil P content but that their contribution varied between P TOT vs. P ILAB . When the spatial variability was computed between grid cells at half‐degree resolution, we found that almost all of the P TOT spatial variability could be explained by BIOG , while BIOG and FARM explained 38% and 63% of P ILAB spatial variability, respectively. Our work also showed that the driver contribution was sensitive to the spatial scale characterizing the variability (grid cell vs. continent) and to the region of interest (global vs. tropics for instance). In particular, the heterogeneity of farming practices between continents was large enough to make FARM contribute to the variability in P TOT at that scale. We thus demonstrated how the different drivers were combined to explain the global distribution of agricultural soil P. Our study is also a promising approach to investigate the potential effect of P as a limiting factor for agroecosystems at the global scale.